Implementation Of Project Based Learning Mode In The Independent Curriculum Towards Improving The Learning Outcomes Of Social Students In Grade VIII - Immanue Natanae Siahaan; Mian Siahaan; Dearlina Sinaga (Jurnal Pendidikan, Sains Sosial, dan Agama, 2023)
This study aims to identify the effect of using the Project Based Learning mode in the Merdeka Curriculum on student learning outcomes in social studies for eighth grade students at SMP Negeri 27 Medan. The study applied a quantitative approach with a quasi-experimental method and a non-equivalent control group design. The research sample consisted of two classes, named class VIII-3 as the experimental group with 30 students and class VIII-2 as the control group with 29 students. The data collection instrument was an objective test consisting of 20 questions administered at the pretest and posttest stages. The results showed an increase in learning ability among students in the experimental class after the Project Based Learning mode was implemented. The average pretest score in the experimental class was 45.67, increasing to 75.42 in the posttest. Meanwhile, the control class obtained an average pretest score of 54.83 and a posttest score of 79.48. The learning completeness in the experimental class reached 83.33%, higher than the control class. The data prerequisite test showed normal and homogeneous results, so the analysis was continued with an Independent Sample T-Test. The statistical analysis results confirmed that there was a significant difference between the two groups, so it can be concluded that the Project Based Learning mode is effective in improving student learning outcomes in social studies